Pedagogical Competence in Early Childhood Education: A Systematic Literature Review on Assessment and Observation Practices - Indah Tri Widiana; Imron Arifin; Evania Yafie; Yudithia Dian Putra (LPPM Institut Pendidikan Nusantara Global, 2026)
Pedagogical competence among early childhood education (ECE) teachers is closely related to teachers’ ability to observe, assess, document, and interpret children’s development. Although assessment is essential in ECE, teachers still face administrative workload, limited assessment literacy, and uneven digital competence. This systematic literature review examines assessment and observation practices as dimensions of teachers’ pedagogical competence. Following PRISMA procedures, 41 peer-reviewed articles published between 2022 and January 2026 were selected from Scopus, Web of Science, Google Scholar, and GARUDA. The main inclusion criteria covered ECE contexts, empirical or rigorous review articles, Indonesian or English language publications, full-text access, and indexed journals. Thematic synthesis was conducted through coding and clustering. The findings show a shift from administrative reporting toward authentic, reflective, and child-centred assessment through continuous observation, pedagogical documentation, portfolios, and digital tools. Assessment quality depends on child development knowledge, observation skill, documentation competence, reflective capacity, and digital competence. This review contributes a conceptual mapping of ECE assessment competence and highlights the need for professional development, ethical digital documentation, and institutional support.